Elevated Plasma Hemoglobin Levels Increase Nitric Oxide Consumption in Experimental and Clinical Acute Pulmonary Thromboembolism - Sertorio, Jonas T.; Neto-Neves, Evandro M.; Dias-Junior, Carlos A. [UNESP]; Sousa-Santos, Ozelia; Kiss, Tamas; Muehl, Diana; Tanus-Santos, Jose E. (Lippincott Williams & Wilkins, 2013)
Objectives: We examined whether experimental lung embolization with autologous blood clots or with the infusion of microspheres increase cell-free hemoglobin levels and nitric oxide consumption by plasma samples from anesthetized lambs. These parameters were also measured in patients with acute pulmonary thromboembolism at baseline conditions and after thrombolysis, and in healthy controls.Design: Controlled animal and clinical studies.Setting: University research laboratory and university hospital.Subjects: Sheep and humans.Interventions: Anesthetized lambs were embolized with intravenous injections of autologous blood clots or repeated injections of 300 m microspheres. Control animals received saline. Blood samples were drawn from patients with acute pulmonary thromboembolism at baseline conditions and after thrombolytic therapy with streptokinase or alteplase.Measurements and Main Results: Hemodynamic measurements were performed and plasma cell-free hemoglobin concentrations were measured. A nitric oxide consumption assay was used to measure nitric oxide consumption by plasma samples. Embolization with blood clots or microspheres increased mean pulmonary artery pressure from similar to 15 to similar to 40 mm Hg in lambs. Both plasma hemoglobin concentrations and nitric oxide consumption increased in proportion to the hemodynamic alterations and correlated significantly. Patients with acute pulmonary thromboembolism had higher plasma hemoglobin concentrations and nitric oxide consumption than healthy controls. Thrombolysis with streptokinase or alteplase further increased both parameters, which peaked 1-3 days after thrombolysis.Conclusions: Our results show consistent evidence indicating a new mechanism involving increased hemoglobin decompartmentalization and augmented nitric oxide consumption, possibly contributing to the hemodynamic derangement of acute pulmonary thromboembolism.
Keywords: acute pulmonary thromboembolism; consumption; hemoglobin; hemolysis; nitric oxide; pulmonary embolism; pulmonary hypertension